1980
DOI: 10.1090/s0025-5718-1980-0583492-2
|View full text |Cite
|
Sign up to set email alerts
|

Additive methods for the numerical solution of ordinary differential equations

Abstract: Consider a system of differential equations x = f(x). Most methods for the numerical solution of such a system may be characterized by a pair of matrices (A, B) and make no special use of any structure inherent in the system. In this article, methods which are characterized by a triple of matrices (A; Bx, B2) are considered. These methods are applied in an additive fashion to a decomposition / = fx + f2 and some methods have pronounced advantages when one term of the decomposition is linear. This article obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…Additive Runge-Kutta. One method of splitting an ODE is to partition the right hand side of an IVP into Λ parts [10,1,21,24]: …”
Section: Formulation Of Idc-arkmentioning
confidence: 99%
See 1 more Smart Citation
“…Additive Runge-Kutta. One method of splitting an ODE is to partition the right hand side of an IVP into Λ parts [10,1,21,24]: …”
Section: Formulation Of Idc-arkmentioning
confidence: 99%
“…In the literature, the definition of ARK for the case of Λ = 2 usually is presented in the form of (2.2) [1,21,10,24]. We reformulate the definition of ARK (Λ = 2) below to suit our analysis.…”
Section: Formulation Of Idc-arkmentioning
confidence: 99%
“…To take into account the special structure of the right hand side of the equation, let us consider the class of Additive Runge-Kutta methods defined in the following way [7].…”
Section: Additive Runge-kutta Methodsmentioning
confidence: 99%
“…Introduction. In a recent article [2] the authors showed that certain pairs of methods may be used in an additive fashion to solve an initial value problem for a system of n differential equations x'=f(t,x),…”
mentioning
confidence: 99%
“…It is also supposed that each element of {J(m)} and {g(m)} is continuous on /. Other assumptions, which are needed to obtain order conditions for additive methods, are detailed in the previous article [2].…”
mentioning
confidence: 99%